2017
DOI: 10.3389/fpls.2017.00763
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Studies In Plant Pathosystems: Toward an Ecological Genomics Approach

Abstract: The emergence and re-emergence of plant pathogenic microorganisms are processes that imply perturbations in both host and pathogen ecological niches. Global change is largely assumed to drive the emergence of new etiological agents by altering the equilibrium of the ecological habitats which in turn places hosts more in contact with pathogen reservoirs. In this context, the number of epidemics is expected to increase dramatically in the next coming decades both in wild and crop plants. Under these consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(145 citation statements)
references
References 111 publications
5
140
0
Order By: Relevance
“…Finally, in agreement with other types of biotic interactions (Bartoli and Roux, ), the majority of QTL mapping studies ( n = 39) revealed a complex genetic architecture associated with plant–plant interactions (Figure ). The quantitative genetic architecture is highly diverse among plant–plant interacting systems, ranging from the identification of few medium‐effect QTLs to the identification of up to tens of small‐effect QTLs (Frachon et al ., ).…”
Section: The Genetics Of Natural Variation Of Plant–plant Interactionssupporting
confidence: 83%
“…Finally, in agreement with other types of biotic interactions (Bartoli and Roux, ), the majority of QTL mapping studies ( n = 39) revealed a complex genetic architecture associated with plant–plant interactions (Figure ). The quantitative genetic architecture is highly diverse among plant–plant interacting systems, ranging from the identification of few medium‐effect QTLs to the identification of up to tens of small‐effect QTLs (Frachon et al ., ).…”
Section: The Genetics Of Natural Variation Of Plant–plant Interactionssupporting
confidence: 83%
“…Most GWAS of plant–microbial interactions have focused on how plant genotype shapes pairwise interactions with a single microbial taxon. Representative examples can be found in the 35 GWAS of direct pathogen challenge collated by Bartoli and Roux (), or the 13 GWAS of disease resistance in maize collated by Xiao et al . ().…”
Section: Previous Workmentioning
confidence: 99%
“…Although regions of 16S ribosomal RNA (rRNA) have been used most often, they afford poor resolution at the level of genera or finer clades. This limitation can be circumvented by using faster‐evolving genes to gain deeper taxonomic resolution (Bartoli and Roux, ). For example, gyraseB sequences allow pathogenic and commensal OTUs within a microbial genus to be distinguished (Barret et al ., ).…”
Section: Workflowmentioning
confidence: 99%
“…It seems common that genetic pathways of R‐genes confer trade‐off with growth or fitness, perhaps due to their large energetic cost (Tian, Traw, Chen, Kreitman, & Bergelson, ). Recently, GWAS of pathogen‐resistant phenotypes have also been performed in other species, including Glycine , Brassica , Medicago , Hordeum , Oryza , Setaria , Sorghum , Pisum , and Zea (reviewed in Bartoli & Roux, ), which may further clarify how common R‐genes are involved in fitness trade‐offs with other traits.…”
Section: Adaptation To Biotic Environmentsmentioning
confidence: 99%